A Review of the Subgenus Chilothorax of the Genus Aphodius (Coleoptera, Scarabaeidae) Occurring in Mongolia, with Description of New Species - Frolov, A.V. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
The Mongolian species of Aphodius Illiger belonging to the subgenus Chilothorax Motschulsky are reviewed. A. kerzhneri Nikolajev and A. mongolaltaicus Nikolajev are placed in the subgenus Chilothorax. Two new synonyms (A. altaicus Nikolajev = A. puntsagdulamae Nikolajev, syn. n.; A. grafi Reitter = A. boreomongolicus Nikolajev, syn. n.) are established. Three new species are described. A key to Mongolian species of Chilothorax is presented.